2000
DOI: 10.1530/eje.0.1430409
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone and mild exercise in combination increases markedly muscle mass and tetanic tension in old rats

Abstract: Objective: A decline of skeletal muscle mass and strength is seen with aging and immobilization. Growth hormone (GH) has been shown to increase muscle mass. In the present study the effects of a combination of mild exercise and GH on skeletal musculature tetanic tension, dry defatted weight (DDW), volume, water, fat and collagen concentrations were investigated in old rats. Design: Recombinant human GH (2.7 mg/kg per day) was injected subcutaneously for 73 days in 21-month-old female rats. Exercised rats ran o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 45 publications
0
8
1
Order By: Relevance
“…23<25 It has also been reported that relatively mild endurance exercise has a synergistic effect on the action of growth hormone on soleus and extensor digitorum longus muscle mass. 26 In the present study ovariectomy may have eliminated the depressive effect that estrogen has on growth hormone or insulin-like growth factor 1 levels. The anabolic effects of these hormones may have then been augmented by the exercise training program, leading to greater hypertrophy than typically observed in endurance training studies using male or intact female rats.…”
Section: Discussionmentioning
confidence: 58%
“…23<25 It has also been reported that relatively mild endurance exercise has a synergistic effect on the action of growth hormone on soleus and extensor digitorum longus muscle mass. 26 In the present study ovariectomy may have eliminated the depressive effect that estrogen has on growth hormone or insulin-like growth factor 1 levels. The anabolic effects of these hormones may have then been augmented by the exercise training program, leading to greater hypertrophy than typically observed in endurance training studies using male or intact female rats.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, experiments done in 21-month-old rats showed that mild physical exercise in treadmill (8 m/min, 1 h/day) in combination with GH administration for 73 days, increased both muscle mass and strength compared with GH by itself (110). However, Marzetti et al showed that short-term treadmill training attenuates age-related skeletal muscle apoptosis and the same effect was not observed with short-term administration of GH in older rats (111).…”
Section: Physical Exercise and Agingmentioning
confidence: 99%
“…The effects of GH administration on muscle mass, strength and physical performance are still under debate [19]. In animal models, GH treatment is very effective at inhibiting sarcopenic symptoms such as muscle atrophy and decreases in protein synthesis particularly in combination with exercise training [88]. The effect of GH treatment for elderly subjects is controversial.…”
Section: Anabolic Hormones In Sarcopenic Musclementioning
confidence: 99%